Import Ban Efficacy on Second-Hand Clothing in the Perspective of Regulatory and Sustainable Development Goals - Amrullah, Dzikri Anik; Akhmaddhian, Suwari; Yuhandra, Erga (Unifikasi : Jurnal Ilmu Hukum, 2024)
The study aims to analyze the ban's effectiveness on secondhand clothing imports in Kuningan Regency. The study utilized research specifications, an empirical legal approach. The findings revealed that Article 47, paragraph (1), of the Trade Law and Regulation of the Minister of Trade Number 40 of 2022; Amendments to Regulation of the Minister of Trade Number 18 of 2021 ban the importing of used apparel. In addition, the regulation is outlined in Article 69 of law number 32 of 2009; environmental protection and waste management, in fact, are not implemented effectively in Kuningan Regency, and second-hand clothing is related to sustainable development goals number 12, namely ensuring sustainable consumption and production patterns. There are seven thrift shops in the vicinity, but they are disregarded by law enforcement, with no supervision at all. To summarize, Kuningan Regency's local administration lacks a stronger legislative framework for law enforcement. As a result, it is critical to create a regional regulation governing imported used garments, as well as to socialize with business actors and the community.